Interactive technologies during implementation of the olympic education into the student educational process - Lidiia Radchenko; Halyna Ivanenko; Iryna Krol; Viktoriia Biletska; Lilia Yasko; Olga Kozhanova; Valentina Ermolova; Aliona Diomina (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
Introduction Shift of priorities and social values in today's society leads to the need for constant improvement of educational process in higher education institutions. The experts note (Bystrova Yu.V., 2015; Gladush V.A. & Lysenko G.I., 2014; Naul R., Binder D., Ivanenko G., 2019) that the outdated practices prevail in today's practical activity of higher educational specialized institutions, the ideas of democratization are not sufficiently implemented. The main problems in the development of higher education institutions are student low motivation to acquire knowledge and drop in attendance. This situation necessitates rethinking of the principles, functions and technologies of managing specialist training in Physical Culture and Sports and, thereupon, develops new approaches to the organization of the pedagogical process in a higher education institution. The analysis of special scientific and methodological literature indicates that today the ways of integration of the Olympic education into the school educational process have been extensively revealed (Armor K, Dagkas S., 2012), the educational potential of the Olympic movement has been elucidated (Bulatov M. & Platonov V., 2018), the importance of integrating Olympic education into the specialist training in Physical Culture and Sports (Radchenko LO, 2016), the activity peculiarities of the Olympic Studies Centers operating as part of the specialized higher education institutions of Ukraine (Zagitova & Radchenko, 2019) have been disclosed, whereas the problem of improving the educational process by integrating Olympic education into the educational process of higher education institutions remains a pressing scientific matter. Today's educational requirements include the training of highly qualified specialists who are able to integrate the theoretical knowledge and practical skills acquired at a higher educational institution into an integral system effectively used in their professional activities. In order to successfully realize personal educational potential of future specialists in Physical Culture and Sports, the development conditions of the qualities such as criticism and non-standard thinking, the ability to produce new ideas and work in a team, etc., must be created. Such tasks are facilitated by the use of interactive learning technologies in the educational process. The working hypothesis is that the use of interactive learning technologies in the study of Olympic education related issues will improve the efficiency of student educational process in higher education institutions preparing future specialists in Physical Culture and Sports. Aim of the Study: to provide the rationale for the use of interactive learning technologies while implementing the Olympic education into the student educational process. Material and methods. Research participants: 12 experts - members of the Olympic Academy of Ukraine, having more than 15 years of pedagogic experience at higher educational institutions, holding managerial positions at sphere-specific educational establishments. 69 students from 8 study groups of the 4th year at the National University of Ukraine on Physical Education and Sport, who major in 0.17 'Physical Education and Sport'. Organization of research. The first step was to determine experts' opinion on the necessity to introduce Olympic education in the student training process. The next step of the study was to determine the educational process efficiency according to I.S. Todorova (Todorova I.S& Pavlenko V.I. 2011). This method employs that the respondents need to answer 20 questions that allow to determine the educational activity efficiency ratio, namely: total educational activity efficiency, motivational subsystem efficiency, operational subsystem efficiency, information subsystem efficiency, and regulatory subsystem efficiency. The level of educational activity efficiency is determined by the quality points earned after calculation. The study was conducted in two cohorts: the 1st cohort is students of the Coach Faculty, and the 2nd cohort is students of the Sport and Management Faculty. Two surveys were undertaken. The first survey was conducted before studying the Olympic Sports. The second one took place in the end of the educational course 'Olympic Sports'. In this paper, such methods as the analysis of literary sources, synthesis and generalization were used to define interactive learning technologies, the use of which helps to enhance the integration of aspects of the Olympic education into the overall educational process. The application of those methods allowed to develop the content and guidelines for the use of the above-mentioned technologies. Statistical analysis. Statistical processing of the data was performed using the Excel 2010 spreadsheet editor (Microsoft, USA, 2010), the average was used. Results: the expediency of Olympic education implementation in the student educational process was studied; the interactive learning technologies that will facilitate the educational process efficiency among the Physical Culture and Sports future specialists were elucidated; the efficiency of the interactive learning technologies in the Olympic education implementation was disclosed. Conclusions: the interactive learning technologies that will felicitate the creation of a highly-qualified specialist in Physical Culture and Sports, namely: interactive cooperative learning technologies (pairwork, trio rotation, 'Carousel', 'Aquarium'); group learning technologies ('Brainstorming', "Decision Tree', 'World Café'); situational modeling technologies ('Six Hats Method', business games); argument technologies ('The PRESSING Method,' 'What? Where? When? How?' debates, etc.); and methodological materials for the students of higher educational institutions of Ukraine were produced, based upon this technology data. The use of interactive learning technologies when integrating Olympic education permits to increase the educational process efficiency and helps to improve student motivation to acquire knowledge.